Development of age appropriate vision function questionnaire for children with visual impairment (CHVI-VFQ) - Meenakshi Wadhwani; Praveen Vashist; Suraj S Singh; Vivek Gupta; Rohit Saxena; Mani Kalaivani; Radhika Tandon (Indian Journal of Ophthalmology, 2022)
Purpose: To develop a new age-appropriate visual function questionnaire for visually impaired children. Methods: The study was conducted in north India in 20,955 (97.3%) children ≤15 years who underwent visual acuity examination. Of these 20,955 children, a total of 722 children were referred with unaided visual acuity less than 6/12 in any eye. Among these referred children, parents in the age group of 5–9 years and children between 10 and 15 years underwent interviews using LV Prasad Functional Visual Questionnaire-20 (LVP FVQ 20) and Indian Visual Functioning Questionnaire-33 (IND VFQ-33). Following this, multiple steps were undertaken that involved expert opinion for the removal of items on basis of zero variance and factor analysis along with calculation of Cronbach's alpha. Results: A Cronbach' alpha of 0.834 was calculated for the younger age group and 0.931 for the higher age group of children. Conclusion: A new robust age-appropriate questionnaire was developed and it was observed that there was a significant change in median score (that was derived for various domains after calculating the median for the items in various domains asked pre- and post-intervention in the form of glasses or surgery) for quality of visual function in the visually impaired children. A significant change in functional vision of visually impaired children (P < 0.005) was observed in both age groups.